2015
DOI: 10.3390/met5020730
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine-Grained Austenitic Stainless Steels X4CrNi18-12 and X8CrMnNi19-6-3 Produced by Accumulative Roll Bonding

Abstract: Austenitic stainless steels X4CrNi18-12 and X8CrMnNi19-6-3 were processed by accumulative roll bonding (ARB). Both materials show an extremely high yield strength of 1.25 GPa accompanied by a satisfactory elongation to failure of up to 14% and a positive strain rate sensitivity after two ARB cycles. The strain-hardening rate of the austenitic steels reveals a stabilization of the stress-strain behavior during tensile testing. Especially for X8CrMnNi19-6-3, which has an elevated manganese content of 6.7 wt.%, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The SPD techniques such as equal channel angular pressing [10], high-pressure torsion [11][12][13], multi-directional forging [14,15], accumulative roll bonding [16][17][18][19], mechanical alloying [20][21][22][23], and friction stir processing [24][25][26] have been successfully used for extreme grain refinement of ASSs.…”
Section: Introductionmentioning
confidence: 99%
“…The SPD techniques such as equal channel angular pressing [10], high-pressure torsion [11][12][13], multi-directional forging [14,15], accumulative roll bonding [16][17][18][19], mechanical alloying [20][21][22][23], and friction stir processing [24][25][26] have been successfully used for extreme grain refinement of ASSs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the role of precipitates for thermal stability is investigated and promising concepts and alloy systems for the future are proposed and discussed. o Ruppert et al [8] subjected the austenitic stainless steels X4CrNi18-12 and X8CrMnNi19-6-3 to the ARB-process and obtained rather high yield strengths of more than 1.25 GPa paired with a high ductility. It was shown that micro-twinning comes into play.…”
Section: Open Accessmentioning
confidence: 99%